2002
DOI: 10.1109/tmag.2002.801799
|View full text |Cite
|
Sign up to set email alerts
|

Recording layer influence on the dynamics of a soft underlayer

Abstract: This paper addresses the recording layer influence on the dynamics of soft underlayer (SUL) films. The static magnetic properties of soft magnetic films magnetostatically coupled to hard magnetic layers are correlated with their dynamic characteristics. The dynamic behavior is studied both theoretically and via direct experimental observation of the magnetization switching in a soft underlayer driven by a recording head. It is found that the dynamics of a SUL can be strongly influenced by magnetostatic couplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The presence of SUL supplies a return flux path from the main pole of the head to the return pole and enables to obtain higher writing fields [4][5][6][7]. If higher writing fields are achieved, materials with higher magnetocrystalline anisotropy energy can be used as recording media, and smaller sized grains can be obtained against superparamagnetic limit and thus higher SNR and areal density can be achieved [8].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of SUL supplies a return flux path from the main pole of the head to the return pole and enables to obtain higher writing fields [4][5][6][7]. If higher writing fields are achieved, materials with higher magnetocrystalline anisotropy energy can be used as recording media, and smaller sized grains can be obtained against superparamagnetic limit and thus higher SNR and areal density can be achieved [8].…”
Section: Introductionmentioning
confidence: 99%
“…In order to attain high signal to noise ratio in perpendicular magnetic recording media, a soft magnetic underlayer, called ''SUL'', is required to suppress the magnetic fluctuation of magnetization in the recording layer. The magnetic properties required for SUL are large saturation magnetization 4pM s and high in-plane magnetic anisotropy field H k [1]. FeCoB/NiFe/Si thin film is one of the hopeful candidates which possess the properties mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…A soft magnetic layer with a high in-plane magnetic anisotropy field H k as well as a high saturation magnetization 4pM s should be developed for a soft magnetic underlayer (SUL) of perpendicular magnetic recording media with a high signal to noise ratio (SNR) [1]. It was reported that the high in-plane uniaxial magnetic anisotropy field in SUL has an important role to attain higher SNR if the easy axis is aligned along the cross-track direction [2].…”
Section: Introductionmentioning
confidence: 99%